2021
DOI: 10.3390/molecules26237354
|View full text |Cite
|
Sign up to set email alerts
|

The Anthelmintic Quassinoids Ailanthone and Bruceine a Induce Infertility in the Model Organism Caenorhabditis elegans by an Apoptosis-like Mechanism Induced in Gonadal and Spermathecal Tissues

Abstract: In continuation of the search for new anthelmintic natural products, the study at hand investigated the nematicidal effects of the two naturally occurring quassinoids ailanthone and bruceine A against the reproductive system of the model nematode Caenorhabditis elegans to pinpoint their anthelmintic mode of action by the application of various microscopic techniques. Differential Interference Contrast (DIC) and the epifluorescence microscopy experiments used in the presented study indicated the genotoxic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Overall, the many exciting findings newly described [6][7][8][9][10][11][12][13] and reviewed [14][15][16][17] in this Special Issue can confidently lead us to a simple conclusion: natural products have a very bright future in the drug research of the 21st century!…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Overall, the many exciting findings newly described [6][7][8][9][10][11][12][13] and reviewed [14][15][16][17] in this Special Issue can confidently lead us to a simple conclusion: natural products have a very bright future in the drug research of the 21st century!…”
Section: Discussionmentioning
confidence: 89%
“…The contributions to this Special Issue demonstrate the huge potential that NPs continue to possess as hits and leads for developing prospective new drugs. Besides a strong focus on the identification and characterization of many new and very promising biologically active NPs against cancer [6][7][8][9][10], infective/parasitic diseases, including their vectors [9,12,13], and diabetic kidney disease [11], it is worth emphasizing that new approaches and methodologies for NP-related drug research are an important focus of this SI. Thus, new methods to identify new bioactive entities in the complex matrices of extracts using hyphenated analytical techniques in combination with computer-aided data analysis tools (e.g., multivariate statistics, molecular networking) are the focus of several articles [6,7,12] utilizing them successfully to identify new bioactive hits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…70 It was also recently reported that 3.31 had an apoptosis-like effect on the reproductive tissues of C. elegans . 71 Such an expansive polypharmacology does not bode well for development of 3.31 as a commercial anthelmintic.…”
Section: Plantsmentioning
confidence: 99%